2019
DOI: 10.1016/j.cell.2019.01.044
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Is a Therapeutic Target for Recovery after Stroke and Traumatic Brain Injury

Abstract: Highlights d CCR5 is differentially upregulated in neurons after stroke d Knockdown of CCR5 induces motor recovery after stroke and improves cognition after TBI d Treatment with an FDA-approved drug, maraviroc induces recovery after stroke and TBI d Human carriers for CCR5delta32 have better outcomes after stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
244
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(276 citation statements)
references
References 57 publications
5
244
1
1
Order By: Relevance
“…Since the birth of the twins, new research has once again shown the effect that suppressing CCR5 can have on the brain, this time demonstrating it to be a therapeutic target to improve recovery from stroke or traumatic brain injury [17]. The study also highlighted a link between the gene and everyday intelligence, with those who are missing at least one copy of the gene appearing to go further in school.…”
Section: The Power Of Resistancementioning
confidence: 96%
“…Since the birth of the twins, new research has once again shown the effect that suppressing CCR5 can have on the brain, this time demonstrating it to be a therapeutic target to improve recovery from stroke or traumatic brain injury [17]. The study also highlighted a link between the gene and everyday intelligence, with those who are missing at least one copy of the gene appearing to go further in school.…”
Section: The Power Of Resistancementioning
confidence: 96%
“…Phase I and II trials using maraviroc (a CCR5 antagonist) treatment after bone marrow transplants showed remarkable ablation of GVHD incidence without side effects. CCR5-32 has been shown to mediate more rapid recovery from stroke (116). Alternatively, homozygous CCR5-32/ 32 carriers are at a fivefold-increased risk for developing encephalitis after infection with West Nile virus (117).…”
Section: Aids-restriction Genes and The Era Of Genome-wide Associatiomentioning
confidence: 99%
“…In a 2019 study, Carmichael and his colleagues showed that levels of CCR5 spike in mice neurons after stroke, and can remain elevated for weeks. 3 This is a problem because CCR5 downregulates the activity of neurons through inhibiting several specific biochemical pathways, including CREB and DLK signalling. These pathways are known to play a role in learning and memory, and the growth of new neurons and neuronal connections.…”
Section: Patients Undergoing Brain-aneurysm Repair Surgery In the Us Andmentioning
confidence: 99%
“…3 This is a problem because CCR5 downregulates the activity of neurons through inhibiting several specific biochemical pathways, including CREB and DLK signalling. 3 This is a problem because CCR5 downregulates the activity of neurons through inhibiting several specific biochemical pathways, including CREB and DLK signalling.…”
mentioning
confidence: 99%